Enhancing Independent Learning and Conceptual Understanding of Integration in Higher Education Mathematics with Photomath - Onesme Niyibizi; Jean Nepomuscene Singirankabo (Scientia Publica Media, 2026)
This study investigated the potential of the Photomath application to promote self-directed learning and integrated conceptual understanding among first-year pre-service mathematics teachers studying at a private higher learning institution during the 2024–2025 academic year. Fastened in a quantitative quasi-experimental survey design, the study targeted 46 purposively selected students pursuing mathematics-related subject combinations. Data were collected using a validated Likert-scale questionnaire designed to capture students’ attitudes, learning autonomy, and levels of conceptual understanding. The instrument demonstrated acceptable internal consistency, with reliability coefficients ranging between 0.76 and 0.84. Statistical analysis using Multivariate Analysis of Variance (MANOVA) revealed statistically significant effects of Photomath usage on students’ attitudes toward mathematics, their conceptual understanding, and their capacity for independent learning. The findings indicated that the app positively influenced learners’ motivation and engagement by providing immediate feedback and step-by-step solution pathways. These features enabled students to follow logical problem-solving processes, thereby supporting deeper engagement with mathematical procedures and concepts. Participants further reported that Photomath facilitated the integration of mathematical ideas through its visual representations, symbolic explanations, and structured guidance. Such affordances supported self-directed learning by allowing learners to verify solutions independently, revisit explanations, and regulate their own pace of learning. While a minority of respondents expressed concerns regarding potential overreliance on the application and the risk of superficial understanding when used uncritically, the overall perceptions remained strongly positive. In conclusion, the study demonstrates that Photomath functions not only as a computational tool but also as a pedagogical aid that supports learner-centered instructional approaches. When used thoughtfully, the application has the potential to enhance conceptual understanding, foster autonomy, and complement formal mathematics instruction in higher education contexts.